Learning Organization, Mewujudkan Sekolah Unggul oleh Manusia Pembelajar di Lingkungan Pembelajar - Syamsul Hadi HM; Muhammad Masyhuri; Nur Hafid (Bidayatuna, 2019)
The low quality of our human resources reflects the low quality of our education system that produces the human resources. We have to reconstruct our educational system. Our educational system we will construct, must be able to build human resources comprehensively, in which the society goes to the learning society and the environment where the society does their activities goes to learning environment. It will be realized by developing Learning Organization. In Learning Organization, the organization supports individuals to keep on learning and enrich their capability as learning society. The actualization of Learning Organization in the learning environment, where all school components interact each other integratedly and each school component functions optimally, so they impulse effectively to the realization of effective school.